Land Landscape Analysis Using the Digital Elevation Model (DEM) Method in the Tetempangan Tourism Object, Mandolang District, Minahasa Regency - Pakasi, Sandra; Rotinsulu, Wiske; Luntungan, Jooudie; Pioh, Diane (PPLH-SDA, Lembaga Penelitian Unsrat Manado, 2022)
Abstract. Sandra E. Pakasi*), Vicky Fransiskus Solum ,Tommy D. Sondakh , Wiske Ch. Rotinsulu, Frangky J. Paat , Jooudie N. Luntungan, Diane D. Pioh. Land Landscape Analysis Using the Digital Elevation Model (DEM) Method in the Tetempangan Tourism Object, Mandolang District, Minahasa Regency. Ekoton 5. 36-43. This study aims to determine the state of the landscape in the Bukit Tetempangan Tourism Object, Mandolang District, Minahasa Regency. This study uses the Digital Elevation Model (DEM) method to obtain the state of the landscape, elevation data, and slope in the Tetempangan Tourism Object area. Data collection and processing techniques using the ArcGis 10.3 application. The results obtained in the Bukit Tetempangan Tourism Object Area have 3 slope classes, 0 - 25% (somewhat flat) with an area of 17.8 Ha, 25 - 40% (a bit steep) with an area of 5.33 Ha, and >40% (very steep) with an area of 14.87 ha and a height of 568 meters above sea level (masl). The total altitude data obtained can reach 1986 points. Thus, at this location, there must be a conservation application to prevent erosion and landslides. Keywords: Analysis, Landscapes, Digital Elevation Model